Enhancing motivation to read and reading abilities in first grade. Issue 1 (2nd January 2020) - Nevo, Einat; Vaknin-Nusbaum, Vered
Abstract: This study examined changes in reading motivation and reading achievement among Hebrew-speaking first graders following an intervention program designed to increase intrinsic reading motivation. The program was delivered by the class teacher and focused on choosing relevant reading materials, providing choices for reading and encouraging social collaboration. Twenty-nine children in the intervention group (IG) were compared with 29 children in the control group (CG) who followed the official reading instruction program. During the year, the IG improved their reading motivation, while the CG declined in self-concept as a reader. Reading achievement improved more in the IG than in the CG. These findings suggest that a reading motivation program should be embedded in the regular reading acquisition curriculum to enhance children's reading motivation and improve their reading skills. Special attention should be paid to prevent a decline in young children's motivation as it may predict their future involvement in reading.